Influence of Limestone Dust on PV Panel Efficiency in a Small Solar Park in Bulgaria - Penka Zlateva; Angel Terziev; Krastin Yordanov; Martin Ivanov; Borislav Stankov (Eng)
The presented paper analyzes the impact of limestone dust accumulation on photovoltaic (PV) panel performance, focusing on the specific surrounding conditions near quarries. The results from the performed field measurements show that high concentrations of limestone dust accumulate significantly faster in these areas, and a hard layer is formed in the presence of moisture. This layer of dust is resistant to removal, even in moderate precipitation and winds with speeds between 6 and 9 m/s, making it a significant problem for the long-term performance of the systems. The analysis revealed that the lack of systematic cleaning of the panels leads to a drop in efficiency of over 20%, with this loss pointedly limiting the return on investment. This study highlights the need for innovative maintenance approaches, such as regular cleaning, use of special coatings and adapting designs to specific environmental conditions. This is essential for the development of strategies to manage, maintain and improve PV systems in areas with high levels of dust pollution.